2010
DOI: 10.1039/c0cp00717j
|View full text |Cite
|
Sign up to set email alerts
|

The application of negative ion electrospray mass spectrometry for the sequencing of underivatized disulfide-containing proteins: insulin and lysozyme

Abstract: Negative ion electrospray mass spectra of the peptides produced by tryptic and chymotrypsin digests of bovine insulin, and from the tryptic digest of lysozyme identify at least 80% of the sequences of these proteins. In particular, negative ion mass spectrometry identifies and positions disulfide moieties, and is the method of choice for identifying this post-translational modification in these two proteins. Intramolecular disulfide functionality is identified by the fragmentation [(M - H)(-)- H(2)S(2)](-) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 8 publications
(11 reference statements)
1
26
0
Order By: Relevance
“…It is known that S–S undergoes marginal cleavage under positive ion CID except with high energy or with metal ions [33]. But S–S undergoes facile cleavage under negative ion CID [3, 34]. Proton abstraction from the C α and C β of the cysteine residue causes diverse fragmentation reactions including the cleavage of disulfide bonds.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that S–S undergoes marginal cleavage under positive ion CID except with high energy or with metal ions [33]. But S–S undergoes facile cleavage under negative ion CID [3, 34]. Proton abstraction from the C α and C β of the cysteine residue causes diverse fragmentation reactions including the cleavage of disulfide bonds.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that in a previous study, where the negative ion cleavages of disulfide containing proteins were investigated [30], it was shown that all four possible product ions were not evident in all cases. This indicates that some care may need to be taken in analyzing the low energy MS/ MS spectra, as all four possible cleavage products may not be observed.…”
Section: Interpretation Of Cross-linking Datamentioning
confidence: 99%
“…Historically, negative ion MS has had limited application for the study of complex systems as the MS/MS data of peptides are often dominated by side chain-induced fragmentations [31,35], whereas spectra in the positive ion mode generally show characteristic backbone cleavages well suited to peptide sequencing. However, equally important and complementary information can be obtained from both ionization modes, and many examples exist whereby negative ion MS allows for mapping of disulfide bonds in proteins with greater ease [30,33,34].…”
Section: Cross-linker Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Electron-based ion dissociations, such as electron-capture dissociation (ECD) [46] and electron-transfer dissociation (ETD) [47], are able to cleave disulfide bonds of protein/peptide ions, in which the cleavage sites of disulfide bonds can be either S-S or C α -S. In addition, upon collision-induced dissociation (CID) in the negative-ion mode, cleavage of disulfide bonds of protein/peptide ions is more favorable compared with backbones [48,49], which could provide unique sequence information by yielding characteristic fragment ions from both S-S and C α -S cleavages. However, in the most widely used positive-ion mode, disulfidebond cleavage is usually suppressed by backbone fragmentations upon CID, resulting in limited sequence information, especially for the regions covered by disulfide bonds.…”
Section: Coupling Of Ec-ms With Liquid-sample Desimentioning
confidence: 99%